Biomechanics-Based Motion Analysis - Ma, Christina Zong-Hao; Li, Zhengrong; He, Chen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Collectively, the studies presented in this reprint have used various validated biomechanical models or proposed novel methods of motion analysis to gain new insights into health-related problems and sports performance.